The Regulations of Protection Tourists in High-Risk Tourism Destination - Sari, Norma; Fajri, Choirul; Winiarti, Sri; Ahdiani, Ulaya; Zulhuda, Sonny (Lembaga Contrarius Indonesia, 2024)
Indonesia is one of the tourism destination countries in the world. The Indonesian government should minimize the risk of tourism activities at high-risk tourist attractions. In the digital era, efforts to optimize tourist protection can be made with artificial intelligence. This study aims to study tourist protection regulations in high-risk tourist areas in Indonesia and compare tourist protection regulations developed by other countries such as the United States of America, Japan, India, and Thailand. This research uses empirical legal legal research, combining normative legal elements with additional empirical data or elements. The results of this research show that there are traveler protection regulations in Indonesia, but their implementation still needs to be improved. Indonesia needs to learn from other countries, such as the United States of America, Japan, India, and Thailand, which have used international standards and implemented Artificial Intelligence. Through the recommended models for using Artificial Intelligence by researchers, it is hoped that they will be able to optimize the protection of tourists at high-risk tourist attractions.